2018
DOI: 10.1101/350819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmodium-specific atypical memory B cells are not part of the long-lived memory response

Abstract: SUMMARY 34A subset of atypical memory B cells accumulates in malaria and several 35 infections, autoimmune disorders and aging in both humans and mice. It has been 36 suggested these cells are exhausted long-lived memory B cells, and their 37 accumulation may contribute to poor acquisition of long-lasting immunity to certain 38 chronic infections, such as malaria and HIV. Here, we generated an immunoglobulin 39 heavy chain knock-in mouse with a BCR that recognizes MSP1 of the rodent malaria 40 parasite, Plasmo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…80 A recent study by P erez-Mazliah et al analyzed the MSP1-specific memory B-cell compartment following Plasmodium infection and found that atypical memory B cells were short-lived and had activated B-cell and plasmablast gene signatures. 84 Mouse studies have not resolved these issues, as age-associated memory B cells can readily respond to Toll-like receptor stimulation, 85,86 whereas in some studies, human atypical memory B cells do not. 87 Clearly, additional studies must be performed to explain the differences in these sets of studies.…”
Section: Atypical Memory B Cells In Plasmodium-infected Individualsmentioning
confidence: 99%
“…80 A recent study by P erez-Mazliah et al analyzed the MSP1-specific memory B-cell compartment following Plasmodium infection and found that atypical memory B cells were short-lived and had activated B-cell and plasmablast gene signatures. 84 Mouse studies have not resolved these issues, as age-associated memory B cells can readily respond to Toll-like receptor stimulation, 85,86 whereas in some studies, human atypical memory B cells do not. 87 Clearly, additional studies must be performed to explain the differences in these sets of studies.…”
Section: Atypical Memory B Cells In Plasmodium-infected Individualsmentioning
confidence: 99%
“…Surprisingly, we did not detect enrichment for memory B and T cells, specifically, which would have suggested anti-malarial immune memory development during one transmission season. This could partially be due to the limited resolution of our gene expression deconvolution technique in distinguishing precisely between memory and naïve lymphocyte populations, the atypical, exhausted phenotype of memory lymphocytes that develop after malaria infection and have unique gene expression profiles 17,18,20,56,57 , or a true defect in memory cell generation over few infections. Future work with more high-resolution techniques such as flow cytometry will be necessary to confirm our results and disentangle these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the identification of PrePC and PreMem populations we included CITEseq 31 Abs specific for the PrePC marker CD69 and CD38 which is upregulated on PreMem cells 15,32,33 . We also included antibodies specific for CD11c and CXCR3 to distinguish atypical B cells from conventional MBCs 34,35 .…”
Section: Because We Can See Stereotypic Selective Sweeps Occurring Am...mentioning
confidence: 99%